Pengembangan Media Pembelajaran Ispring Suite 9 pada Mata Pelajaran Pendidikan Agama Islam dalam Peningkatan Hasil Belajar Siswa - Umroh, Hijjatul; Sanjaya, Budi; Ridwan, Ahmad (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2023)
This research is Research and Development (R&D) research with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model developed by Lee & Owens. With data analysis techniques, namely qualitative and quantitative data obtained from product quality assessment questionnaires and hypothesis testing using one-way ANOVA. This research shows the level of suitability of the iSpring Suite 9 learning media in the subject of Islamic Religious Education, the average assessment by material experts is 4.61 indicating the "Very Appropriate" category, while the average score by media experts is 4.71, which is included in the "Very Appropriate" category. Very Worth It.” As for eligibility, teachers obtained an average of 4.57 in the "Very Appropriate" category, namely in the range 4.2 – 5.0. The results of hypothesis testing show results with a significance level of 0.000 ≤ 0.05. So, Ho is rejected and there is a significant difference between the learning outcomes of students who use the iSpring Suite 9 learning media and those who do not use the iSpring Suite 9 learning media in Islamic Religious Education subjects in improving student learning outcomes.